2016
DOI: 10.1177/2047487316655910
|View full text |Cite
|
Sign up to set email alerts
|

Higher education is associated with reduced risk of heart failure among patients with acute myocardial infarction: A nationwide analysis using data from the CVDNOR project

Abstract: We observed an inverse association between educational level and risk of HF. More efforts in preventing this severe complication of AMI among less educated patients may help to reduce the socioeconomic gap in survival following coronary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…21,22 For the management of ACS in an environment of incurring significant out-of-pocket expenditure, these factors may have influenced the use of some treatments among patients with less formal education. 4,12,23 The findings from the current study are consistent with previous Chinese reports. 24,25 Whether China's recent progress towards universal health insurance has positively influenced such observations is not clear.…”
Section: Discussionsupporting
confidence: 92%
“…21,22 For the management of ACS in an environment of incurring significant out-of-pocket expenditure, these factors may have influenced the use of some treatments among patients with less formal education. 4,12,23 The findings from the current study are consistent with previous Chinese reports. 24,25 Whether China's recent progress towards universal health insurance has positively influenced such observations is not clear.…”
Section: Discussionsupporting
confidence: 92%
“…However, the possible mediators and mechanisms for these causal associations were not examined by our MR analysis. The reasons might be that the gradients in education or income influenced the existing gradients of dietary behavior, unhealthy lifestyle factors, environmental factors, and cognitive ability to disease, ultimately resulting in disparate stone outcomes [ 45 , 46 ]. Furthermore, our MR outcomes showed no significant associations of smoking, alcohol consumption, glucocorticoid use, physical activity, sedentary leisure hours, and diet with the risk of kidney stones.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, consistent evidence suggests that higher educational attainment is correlated with a decreased lifetime risk of cardiovascular diseases ( 23 ). Regarding specific cardiovascular conditions, research demonstrated an inverse relationship between educational attainment and the likelihood of heart failure in patients with coronary heart disease ( 24 ). This highlights the potential benefit of implementing preventive measures for individuals with lower education levels to address survival disparities.…”
Section: Discussionmentioning
confidence: 99%